Comparison of the Legal Regulation of Adultery as Social Control in Society: A Comparison Between Indonesia, Malaysia, Brunei Darussalam, and Turkey - Lestiawati, Ida; Maisa, Maisa; Manan, Abdul (SASI, 2024)
Introduction: Differences in adultery regulations in various countries in the world can be different, one of which is due to the ideology adopted by each country. Regulations related to adultery actually have relevance to state ideology and the values held and lived by society, including religious values.Purpose of the Research: This research aims to analyze and compare adultery regulations based on the values and ideology that apply in a country by comparing adultery regulations between Indonesia, Malaysia, Brunei Darussalam, and Turkey.Method of Research: This research is normative legal research by prioritizing historical, conceptual, legislative and comparative approaches.Results of Research: The results of the research confirm that the development of adultery regulations in Indonesia has not been substantively facilitated since it was regulated in the WvSNI and even passed into the Criminal Code in 1946. This is because what is regulated in the Criminal Code as an official translation of Dutch criminal law is only an overspel that if translated into Indonesian is closer to the act of infidelity and not adultery. The regulation of adultery in the new national criminal law is officially regulated in the New Criminal Code, especially in Article 411 of the New Criminal Code, which is actually in accordance with the meaning of the offense of adultery in accordance with the values and culture of Indonesian society. Differences in the regulation of adultery in each country, especially countries with a majority Muslim population. This is a necessity because differences in adultery regulations in each country depend on the ideology adopted by each country. However, in general, in societies where the majority are Muslim, adultery is classified as a disgraceful act that deserves criminal sanctions as applied in Indonesia, Malaysia and Brunei Darussalam, whereas Turkey, even though the majority of the population is Muslim, is based on a secularist view, only regulating adultery within the realm of law. private.